Primary health care and the social determinants of health: essential and complementary approaches for reducing inequities in health. Issue 8 (22nd November 2009) - Rasanathan, Kumanan; Montesinos, Eugenio Villar; Matheson, Don; Etienne, Carissa; Evans, Tim
Abstract : Increasing focus on health inequities has brought renewed attention to two related policy discourses - primary health care and the social determinants of health. Both prioritise health equity and also promote a broad view of health, multisectoral action and the participation of empowered communities. Differences arise in the lens each applies to the health sector, with resultant tensions around their mutual ability to reform health systems and address the social determinants. However, pitting them against each is unproductive. Health services that do not consciously address social determinants exacerbate health inequities. If a revitalised primary health care is to be the key approach to organise society to minimise health inequities, action on social determinants has to be a major constituent strategy. Success in reducing health inequities will require ensuring that the broad focus of primary health care and the social determinants is kept foremost in policy - instead of the common historical experience of efforts being limited to a part of the health sector.